Preventing corruption within government procurement: Constructing the disciplined and ethical subject. (May 2015) - Neu, Dean; Everett, Jeff; Rahaman, Abu Shiraz
Abstract: This paper examines the role of internal controls and monitoring practices in corrupt contexts and how these controls and practices shape the ethics and moral behaviors of organizational actors. Specifically focusing on corruption in government procurement and drawing on the insights of Michel Foucault and Gilles Deleuze, the paper proposes that effective anti-corruption practices depend upon an understanding and analysis of the practices and politics of visibility, and that effective 'luminous arrangements' have the potential to discourage corrupt practices and influence ethics within organizations. While such arrangements do not necessarily prevent corrupt practices, they do encourage certain actions and reactions among organizational actors, suggesting that organizational actors are at one and the same time free and autonomous, yet subject to and constructed by anti-corruption practices. These practices are thus both disciplinary and productive, affecting individuals in specific ways, while also benefitting the organizations for whom they work.